MENINGKATKAN PEMAHAMAN KONSEP IPA MELALUI PENERAPAN METODE EKSPERIMEN DI KELAS III SDN 31 MATARAM - Hadiah Tullah, Nanda; Rachmatul Hidayati, Vivi; Mardiana, Nana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study uses the Classroom Action Research (CAR) method which aims to describe the improvement of understanding of science concepts by applying the Experiment method. The design of this study uses the Kemmis and Mc Taggart model which is carried out in two cycles. Participants in this study were 15 students of grade III SDN 31 Mataram consisting of 8 male students and 7 female students. This study used data collection techniques in the form of evaluation tests and non-test techniques in the form of observation, while the data analysis technique used was quantitative descriptive. The results of the study in cycle I with a percentage reaching 67% of the total number of 15 students. In cycle I, students who did not meet the KKM were 5 students or around 33% in the sufficient category. In cycle II, students who met the KKM (70) were 13 students or 86% of the total number of 15 students with the good category. In cycle II, students who did not meet the KKM were 2 students or only 14%. Thus, through the application of the experimental method, understanding of science concepts can be improved.